PRIORITAS PENGGUNAAN DANA DESA DALAM MEWUJUDKAN PEMBANGUNAN NAGARI CUPAK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK PROVINSI SUMATERA BARAT TAHUN 2020-2022 - Habiballoh, Adinda Mustika; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Prioritizing the utilization of village funds: Based on Government Regulation Number 60 of 2014, the Village Fund sourced from the State Budget is allocated to villages through the district/city's Regional Budget. It is intended for financing governance, development implementation, community development, and empowerment. The utilization of the Village Fund is essentially the right of the Village Government, aligned with the authority and priority needs of the local village community while upholding principles of justice. The objective of this research is to determine the priorities of Village Fund usage in Nagari Cupak. The theory utilized is the Second Generation Policy Implementation with a Bottom-Up and Top-Down Approach. The research approach employed is qualitative research. The research location is Nagari Cupak, Gunung Talang Sub-district, Solok Regency, West Sumatra Province. The type and source of data used are secondary data obtained from the Village Budget (APBDes), Village Medium-Term Development Plan (RKPDes), and Village Long-Term Development Plan (RPJMDes). The data collection technique involves documentation. The results of this study entail the alignment between national priorities, the needs of the Nagari Cupak community, and budget adjustments to fulfill the community's needs in implementing the priorities of Village Fund utilization. The research findings indicate that the priority of Village Fund utilization in Nagari Cupak, when examined through the Top-Down approach, is the BLT (Direct Cash Assistance) program, where the central government reallocates Village Funds to address Covid-19. Conversely, when analyzed through the Bottom-Up approach, the Nagari Cupak government prioritizes the utilization of Village Funds for the BUMNAG (Badan Usaha Milik Nagari) program. Keywords: Village Funds, Development and Priorities.